2008
DOI: 10.1073/pnas.0705896105
|View full text |Cite
|
Sign up to set email alerts
|

Germ-line mutations, DNA damage, and global hypermethylation in mice exposed to particulate air pollution in an urban/industrial location

Abstract: Particulate air pollution is widespread, yet we have little understanding of the long-term health implications associated with exposure. We investigated DNA damage, mutation, and methylation in gametes of male mice exposed to particulate air pollution in an industrial/ urban environment. C57BL/CBA mice were exposed in situ to ambient air near two integrated steel mills and a major highway, alongside control mice breathing high-efficiency air particulate (HEPA) filtered ambient air. PCR analysis of an expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
203
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(220 citation statements)
references
References 75 publications
11
203
0
6
Order By: Relevance
“…The difference between the adduct levels in testes and lung tissue was found previously [Yauk et al, 2008]. It is possible that B[a]P does not reach the testes as well as lung tissue after exposure by oral gavage, and/or that testes may contain lower concentrations of enzymes converting B[a]P into DNA binding derivatives.…”
Section: Discussionsupporting
confidence: 54%
“…The difference between the adduct levels in testes and lung tissue was found previously [Yauk et al, 2008]. It is possible that B[a]P does not reach the testes as well as lung tissue after exposure by oral gavage, and/or that testes may contain lower concentrations of enzymes converting B[a]P into DNA binding derivatives.…”
Section: Discussionsupporting
confidence: 54%
“…39 These and our findings are in line with the global hypermethylation found in the sperm of mice exposed for 3 weeks to particulate air pollution of urban/ industrial source, in which PAH exposure was confirmed by the presence of elevated PAH-DNA adduct levels in the mice lungs. 15 Moreover, following in vitro chronic exposure to B[a]P, global DNA hypermethylation was associated to DNMT1 overexpression in mouse embryonic fibroblasts. 14 DNMTs (chiefly DNMT1) were found upregulated during DNA damage and bind with high affinity to DNA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…13 Global DNA hypermethylation following in vitro chronic exposure to B[a]P was recently revealed in mouse embryonic fibroblasts and was associated to mutation as a consequence of genetic instability. 14,15 PBLs, although not considered target cells for PAH(B[a]P)-induced lung tumorigenesis, can be easily obtained from human subjects and their genetic (PAH(B[a]P)-DNA adducts) and epigenetic alterations (methylation) are correlated with levels in target tissues (e.g., lung). [16][17][18] Moreover, high levels of adduct and micronuclei (as markers of chromosome instability 19 ) and p53 hypomethylation in PBLs are predictive of lung cancer risk.…”
mentioning
confidence: 99%
“…Consequently, the two main roles of DNA methylation are thought to be maintenance of genome stability (Eden et al, 2003) and control of gene transcription (Bird, 2002). In higher organisms, which have functionally different cell types, DNA methylation is thought to be important in the control of gene expression, and changes in DNA methylation can dramatically affect chromatin structure and genome stability (Yauk et al, 2008). Franco et al (2008) indicated that reactive oxygen spemultistage process of carcinogenesis by both genetic and epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%